Evolution of global electricity markets : new paradigms, new challenges, new approaches - Sioshansi, Fereidoon P. (Fereidoon Perry) (Elsevier/Academic Press, 2013)
Get the latest on rapidly evolving global electricity markets direct from the scholars and thought leaders who are shaping reform. In this volume, dozens of world-class experts from diverse regions provide a comprehensive assessment of the relevant issues in today's electricity markets. Amid a seething backdrop of rising energy prices, concerns about environmental degradation, and the introduction of distributed sources and smart grids, increasingly stringent demands are being placed on the electric power sector to provide a more reliable, efficient delivery infrastructure, and more ...